Normal transaminases in obese patients with metabolic associated steatohepatitis (MASH): a cohort of Peruvian patients - Lozano, Adelina (2022)
Introduction: Metabolic associated steatohepatitis (MASH) is one of the most frequent causes of chronic liver disease. Liver transaminases are important biomarkers to measure liver injury, however, a proportion of patients with MASH may present with normal levels of transaminases. The levels of serum transaminases may not correlate with the severity of histopathological changes. Objective: We aimed to identify the frequency of normal transaminases in obese patients with MASH, as well as to describe the clinical, biochemical and histological characteristics in this specific group of patients. Materials and methods: A retrospective cross-sectional study was conducted in the bariatric surgery service of a private clinic. Obese patients older than 18 years with a body mass index (BMI) >30Kg/m2 and 2 co-morbidities undergoing a gastric sleeve surgery were included. Measurement of biochemical routine laboratory exams was performed. Insulin resistance was calculated using the homeostasis evaluation model (HOMA-IR). All patients underwent liver biopsies prior to surgery and the diagnosis of MASH was based on the Brunt criteria. Results: 159 obese patients with MASH were included, of which 47.2% had normal transaminases and 52.8% elevated transaminases. Factors associated with alteration in transaminases were: being male OR=4.02 (95% CI: 2.03-7.96; p<0.01), diagnosis of type 2 diabetes mellitus OR=4.86 (95% CI: 1.97- 11.95; p<0.01) and levels of GGT >50 IU/L OR=7.50 (95% CI: 3.40-16.56; p<0.01). The values of HOMA-IR and GGT were significantly higher in the group of high transaminases (p<0.01). Differences in the degree of fibrosis were not associated with transaminases levels. Conclusion: In conclusion we found that the frequency of normal transaminases was 47.2% in obese patients with MASH. Factors associated with elevation in liver enzymes were being male, diagnosis of diabetes mellitus and elevation in GGT levels. The degree of fibrosis was not associated with elevations in liver transaminases. These findings suggest that transaminases levels alone are not accurate markers to assess liver injury, as they do not necessarily correlate with histological liver damage.